Audiological Outcome in Myringoplasties with an Intact Ossicular Chain: Is there a Difference between Chronic Otitis with or without Cholesteatoma? - Sarolli, Eduardo de Barros; Schlegel-Wagner, Christoph; Linder, Thomas Edwin (International Archives of Otorhinolaryngology, 2020)
Introduction Chronic otitis media (COM) with a central perforation or a concomitant cholesteatoma are both inflammatory lesions, however, with different etiologies. Both entities may present with an intact chain, and the final reconstruction is quite similar. Does it also apply for the hearing outcome?Objectives In a retrospective analysis, we investigated the preoperative hearing and the final hearing outcome of two groups of patients: those with COM and those with cholesteatoma, and compared various factors.Methods Patients operated between 2010 and 2019 were entered prospectively into a research database, and the integrity of the ossicular chain, the extent of the cholesteatoma, and the findings on computed tomography (CT) scans were retrospectively analyzed and correlated to the final hearing outcome.Results Out of 210 tympanoplasties for COM, 162 (80%) presented with an intact chain, and 85 (40%) ears could be analyzed. Out of 283 cholesteatoma surgeries, 53 (19%) ears presented with an intact chain. The preoperative air-bone gap (ABG) was worse in the COM group, but the postoperative ABG over the frequencies of 0.5 kHz and 4 kHz was the same (10 dB to 12 dB) in both groups, and remained within 20 dB in 90% (40 and 78 patients, respectively). The extension of the disease was rather limited in the cholesteatoma group (stages Ch1a and 1b), and better pneumatization and ventilation were beneficial for a good result. Postoperatively, the frequency of 4 kHz had the largest ABG (14 dB and 18 dB).Conclusion Overall, 80% of the patients with COM and less than 20% of those with cholesteatoma had an intact and mobile chain at surgery. Using equivalent surgical techniques for the tympanoplasty, the final outcome was almost the same for both groups, with a mean ABG of 10 dB to 12 dB.
Keywords: chronic otitis media; cholesteatoma; hearing outcome; air-bone gap; tympanoplasty